WEBOMETRIC STUDY OF PRIVATE UNIVERSITIES IN BANGLADESH - Islam, Md. Anwarul; Alam, Md. Saiful (Malaysian Journal of Library and Information Science, 2017)
There have been substantial studies conducted on webometrics, especially on the impact of websites and the web impact factor. The present study analysed the websites of private universities in Bangladesh according to the webometrics indicator. It examines and explores the 44 private university websites in Bangladesh and identifies the number of web pages and link pages, and calculates the Overall Web Impact Factor (WIF) and Absolute Web Impact Factor (WIF). In a crosssectional study, all the websites were analysed and compared using AltaVista search engine. The websites were then ranked based on these webometric indicators. The study revealed that some private universities in Bangladesh have higher number of web pages but their link pages are very small in number, thus the websites fall behind in their Overall WIF, self link, external links and Absolute WIF. Finally, it is showed that these universities did not have much impact factor on the web and were not known internationally. The major reasons are discussed and suggestions to overcome the problems are presented.